THE ROLE OF DISKOPERINDAG IN SUPPORTING THE SUSTAINABILITY OF MSME IN BIMA CITY - Siti Fatimah; Rafiuddin Rafiuddin; Muhammad Rasyad Al Fajar (Nurul Jadid University, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in supporting economic growth, creating jobs, and improving community welfare. In Bima City, the MSME sector has experienced rapid growth, with the number of business units increasing significantly in recent years. However, despite having great potential, MSMEs in Bima City still face various challenges, such as limited access to capital, lack of use of digital technology, and low competitiveness against products from outside the region.This study aims to analyze the role of the Cooperatives, Industry, and Trade Service (Diskoperindag) of Bima City in empowering MSMEs to improve the sustainability and competitiveness of their businesses. The research method used is a qualitative approach with data collection techniques through interviews, observations, and literature studies. The results of the study show that Diskoperindag of Bima City has various strategic programs in supporting MSMEs, including business management training, digital marketing, product innovation, and facilitation of access to People's Business Credit (KUR) and business certification. In addition, collaboration with financial institutions and product promotion through exhibition events also contribute to expanding the MSME market.However, there are several obstacles in the implementation of the program, such as budget constraints, lack of ongoing assistance, and low awareness of MSME actors regarding the benefits of the available programs. Therefore, it is necessary to increase the effectiveness of the empowerment program through optimizing coordination between the government, business actors, and related stakeholders. In conclusion, the Bima City Trade and Industry Office plays an important role in improving the sustainability of MSMEs, but further efforts are still needed to overcome the challenges faced so that the MSME sector can develop more optimally and be highly competitive